The mortality of COVID-19 in CML patients from 2020 until 2022: results from the EPICOVIDEHA survey - El-Ashwah, Shaimaa; Salmanton-García, Jon; Bilgin, Yavuz M; Itri, Federico; Žák, Pavel; Weinbergerová, Barbora; Verga, Luisa; Omrani, Ali S; Silva, Maria Gomes da; Szotkowski, Tomáš; Marchetti, Monia; Buquicchio, Caterina; et al. (Leukemia & lymphoma, 2024)
Since the beginning of the COVID-19 pandemic, there has been an overall improvement in patient mortality. However, haematological malignancy patients continue to experience significant impacts from COVID-19, including high rates of hospitalization, intensive care unit (ICU) admissions, and mortality. In comparison to other haematological malignancy patients, individuals with chronic myeloid leukemia (CML) generally have better prognosis. This study, conducted using a large haematological malignancy patient database (EPICOVIDEHA), demonstrated that the majority of CML patients experienced mild infections. The decline in severe and critical infections over the years can largely be attributed to the widespread administration of vaccinations and the positive response they elicited. Notably, the mortality rate among CML patients was low and exhibited a downward trend in subsequent years. Importantly, our analysis provided confirmation of the effectiveness of vaccinations in CML patients.
Keywords: Chronic myeloid leukemia; tirosine kinase inhibitor; Hematologic Neoplasms; Hospitalization; neoplasia; COVID-19; hospitalizace; Pandemics; Humans; chronická myeloidní leukemie; pandemie; vaccines; hematologické nádory; lidé; SARS-CoV-2; Leukemia, Myelogenous, Chronic, BCR-ABL Positive